Pengaruh Angka Kematian Bayi, Angka Partisipasi Murni, Rasio Ketergantungan terhadap Indeks Pembangunan Manusia Provinsi Jawa Timur - Zia Azuro Zuhairoh (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
The human development index is indicator to measure efficacy of human development. The human development index is composed of life expectancy at birth (health factor), average length of school and school life expectancy (education factors), and also gross national per capita (economic factor) expenditure. The human development index in East Java Province in 2016 was below national rate and still of medium status. This achievement depends on the factors that influence it. The goal was to analyze the effect of infant mortality rate, net enrollment rate for elementary school, and dependency ratio on human development index of East Java Province. This study includes the type of analytical research with non-reactive method. Sample size was 29 districts and 9 cities in East Java Province 2016. The analysis used multiple linear regression. The study showed that the three independent variables are simultaneously affect human development index (p-value = 0.000). Partially, the net enrollment rate for elementary school (p-value = 0.164) was insignificant whereas infant mortality rate (p-value = 0.0000) and dependency ratio (p-value = 0.000012) had negative affect and significant to human development index. The conclusion of this research is the value of human development index can be increase while decreasing infant mortality rate and dependency ratio.